Chinese Version of Psychometric Evaluation of Self-Reflection and Insight Scale on Taiwanese Nursing Students - 陳淑月(Shu-Yueh Chen); 賴貞君(Chen-Chun Lai); 張惠美(Hui-Mei Chang); 徐慧真(Hui-Chen Hsu); 白香菊(Hsiang-Chu Pai) (The Journal of Nursing Research, 2016)
BACKGROUND:Self-reflection (also known as reflection) is an internal process that is difficult to perceive or assess. An instrument that is able to measure self-reflection may serve as a resource for educators to assess the learning process of students and to tailor education approaches to student needs. PURPOSE:The aim of this study was to translate the Self-Reflection and Insight Scale (SRIS) into Chinese and evaluate its psychometric properties for use with Taiwanese nursing students. METHODS:For this cross-sectional study, nursing students were recruited from two nursing schools in southern Taiwan in two phasesPhase 1, which included 361 fourth-year students, and Phase 2, which included 703 fifth-year students. Data were collected in December 2012 and May 2013 using the Chinese version of the SRIS (SRIS-C), Taiwan Critical Thinking Disposition Inventory, and the Perceived Identity as a Nurse Questionnaire, which was developed by the author. In Phase 1, exploratory factor analysis was used to explore the factor structure of the SRIS-C in the fourth-year student participants. In Phase 2, confirmatory factor analysis was used to determine the fitness of the model for the fifth-year student participants. RESULTS:Eight items were deleted from the original SRIS to create the SRIS-C. Thus, the Chinese-version measure had 12 items and two factors (self-reflection and insight) that fit the data well. The Cronbach’s alpha coefficients for the total scale and its two subscales were .79, .87, and .83, respectively. The 3-week test–retest reliability was .74. SRIS-C scores correlated significantly with scores on the Taiwan Critical Thinking Disposition Inventory and the Perceived Identity as a Nurse Questionnaire, indicating good convergent validity for the SRIS-C. CONCLUSIONS:The current study showed that the SRIS-C has sound psychometric properties. This instrument provides nurse educators with information that may be used to evaluate the self-reflection and insight of students and to develop interventions to effectively improve these skills in Chinese-language-based nursing education.